Analisis Kepuasan Pengguna Mobile JKN Di Kantor Cabang BPJS Kesehatan Kabupaten Grobogan - Dena Nur Rahmatika; Rani Tiara Desty; Lindra Anggorowati (Indonesian Journal of Health Community, 2024)
Grobogan residents feel burdened by the registration procedure which takes a long time. The research aims to determine the relationship between the success of the information system and the satisfaction of Mobile JKN users at the Grobogan Regency BPJS Health Branch Office. The method uses a cross-sectional quantitative approach. Data analysis used the Chi-square test. The success of the Mobile JKN system, the result of the system quality variable, is that there is no relationship because the p-value is 0.262. The result of the information quality variable is that there is no relationship because the p-value is 0.361. The result of the service quality variable is that there is no relationship because the p-value is 0.771. The result of the variable system use is that there is no relationship because the p-value is 0.57. The result of the user profit variable is that there is no relationship because the p-value is 0.57. The five information system success variables have no relationship with Mobile JKN user satisfaction at the BPJS Health Branch Office because the p-value is <0.05. Suggestions from BPJS Health Grobogan Regency Branch can improve the JKN Mobile application services.